2019
DOI: 10.1088/1757-899x/537/6/062011
|View full text |Cite
|
Sign up to set email alerts
|

The results of the differential mineral fertilization in the automatic mode according to the task map

Abstract: Off-line differential fertilization is one of the science-intensive technological processes in the precision farming system. The process ensures the change of the norm during the movement of the device in the field in the automatic mode according to the task map compiled on the personal computer for the elementary parts of the field. In the conditions of Western Siberia, studies have been conducted to identify the effectiveness of a differentiated method of applying nitrogen fertilizers for the planned yield o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Adaptive landscape farming technologies were also developed, which contributed to the disclosure of the potential of soils involved in agriculture [5,6]. Currently, there are zonal systems of crop rotation, tillage, fertilizers, and plant protection [7,8]. The set of results of the work of breeders, geneticists, farmers, and agricultural chemists ensured the agriculture advancement far to the north and east of Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive landscape farming technologies were also developed, which contributed to the disclosure of the potential of soils involved in agriculture [5,6]. Currently, there are zonal systems of crop rotation, tillage, fertilizers, and plant protection [7,8]. The set of results of the work of breeders, geneticists, farmers, and agricultural chemists ensured the agriculture advancement far to the north and east of Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, almost immediately they had to admit that the fertilizer system works effectively on the medium agricultural background, where it is planned to obtain a yield of grain crops of no more than 4.0 t/ha. At high agricultural backgrounds, providing yields of more than 5.0 t/ha, its efficiency decreases, and as the experience of many years of research has shown, the genetic characteristics of varieties are a limiting factor [8,9]. This is most clearly manifested in the grain biochemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…This explains the strong variability in the properties of soils formed within the same natural and climatic zone. Thanks to the development of science and technology, new varieties of agricultural crops were created, zonal systems of tillage and fertilizers were developed [1][2][3][4]. On their basis, a system of Siberian agriculture was developed, which considered the harsh climatic conditions and low-fertile soils.…”
Section: Introductionmentioning
confidence: 99%